PENJATUHAN SANKSI PIDANA BAGI PELAKU PENGANIAYAAN BENTUK PENYERTAAN (STUDI PUTUSAN NOMOR 111/Pid.B/2021/PN MBO): Imposition of Criminal Sanctions for Perpretators of Abuse in The Form of Participation (Study Case Number 111/Pid.B/2021/PN.MBO) - Fonataba, Orin Tesa Woisiri; Wangga, Maria Silvya E. (AMICUS CURIAE, 2024)
This scientific article follows up on the Meulaboh District Court Decision Number 111/Pid.B/2021/PN MBO abuse committed by more than one person, known as participation. The imposition of criminal sanctions occurs to provide justice for victims and overcome the possibility of other people commiting the same crime. Qualifications for form of inclusion of perpetrators of abuse and criminal sanctions for perpetrators of abuse in the form of participation according to theory of punishment will be the focus of discussion in this article. The result of the research show that the perpetrator of the abuse  fulfills the form of inclusion of the perpetrator (plegen) because all elements of the criminal act of abuse fulfilled and perpetrators abuse forms participation of were sentenced to prison for 4 (four) months, this is not in accordance with contemporary theory and relative theory which requires perpetrators to be sentenced  to 2 (two) years and 8 (eight) months. It is hoped that every law enforcer can be more careful in deciding Articles and consider the purpose of punishment for maximum sanction.